2021
DOI: 10.1590/0037-8682-0891-2020
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cerebrospinal Fluid for the Diagnosis of Neuroinvasive Dengue, Zika, and Chikungunya: A 19-year systematic review

Abstract: Introduction: Cerebrospinal fluid analysis contributes to the diagnosis and neuropathogenesis of neuroinvasive arboviruses. Neurological complications caused by dengue, Zika, and chikungunya infections have high clinical relevance because of their high potential to cause death or neurological deficits. We aimed to evaluate the use of cerebrospinal fluid assays for diagnostic support in neurological disorders associated with dengue, chikungunya, and Zika infections. Methods: A systematic review was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Several reports have shown that CHIKV RNA can be detected in body fluids other than serum, such as saliva [ 26 , 28 , 29 ], urine [ 24 , 28 , 29 , 34 ], sperm [ 24 , 29 ], vaginal secretions [ 29 ], placenta or amniotic fluid [ 35 ], breast milk [ 36 ], synovial liquid [ 37 ] and cerebrospinal fluid [ 38 , 39 ]. Infectious CHIKV has also been detected in the saliva of mice, monkeys and humans [ 27 ], raising concerns about the potential for non-vector-borne transmission [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that CHIKV RNA can be detected in body fluids other than serum, such as saliva [ 26 , 28 , 29 ], urine [ 24 , 28 , 29 , 34 ], sperm [ 24 , 29 ], vaginal secretions [ 29 ], placenta or amniotic fluid [ 35 ], breast milk [ 36 ], synovial liquid [ 37 ] and cerebrospinal fluid [ 38 , 39 ]. Infectious CHIKV has also been detected in the saliva of mice, monkeys and humans [ 27 ], raising concerns about the potential for non-vector-borne transmission [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data relating to prolonged excretion are potentially not generalizable to endemic settings where viremia is shorter, particularly in the setting of reinfection. PCR is used less frequently on CSF than serologic tests (though it is unclear whether this relates to access or better diagnostic sensitivity) [37]. Mosquitos and both fresh and formalin-fixed paraffin-embedded human tissues are also described [89,95,96].…”
Section: Specimens For Molecular Diagnosismentioning
confidence: 99%
“…Antibody detection is the commonest diagnostic modality requested to support the clinical diagnosis of DENV infection. It is generally performed on serum or plasma, though dried blood spots of venous or capillary blood, saliva and CSF can be used [37,84,86,87,[141][142][143]. Use in diagnosis is hampered by the degree of cross-reactivity between flaviviruses of the viral E protein in serologic assays, against which most IgG and IgM antibodies used in diagnosis are directed [67].…”
Section: Antibody Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of inflammatory biomarkers in the CSF can provide valuable information about the immune response in the neuroinvasive arboviruses DENV and CHIKV [10]. In addition, neurological symptoms are not specific for neuroarboviruses, and the routine CSF analysis is frequently normal, making diagnosis difficult [18,19]. This study aims to evaluate neopterin and CXCL-10 biomarkers in CSF samples for the diagnosis of neuroinvasive DENV and CHIKV.…”
Section: Introductionmentioning
confidence: 99%